1977
DOI: 10.1111/j.1445-5994.1977.tb04676.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Verapamil on Experimental Myocardial Ischaemia with a Particular Reference to Regional Myocardial Blood Flow and Metabolism*

Abstract: The effects of verapamil on epicardial ST segment elevation, regional myocardial metabolism and collateral blood flow were studied in open-chest anesthetized dogs following left anterior descending coronary artery occlusion. Collateral blood flow was measured by radioactive microspheres (15 +/- 5 micron diameter) and regional metabolism was studied by measuring lactate concentration in venous blood draining the infarcting myocardium. Verapamil (0-2 mg/kg intravenously) produced a significant reduction (50-60%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

1979
1979
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…'9 Verapamil dilates the coronary vasculature,38 but no consistent effect on blood supply to an ischemic area has been demonstrated. 21 38 Diltiazem has been shown to improve blood flow to partially perfused areas in the pig,39 but no effects on blood flow to severely ischemic areas were seen. In view of these findings and the minimal collateral circulation in the swine heart,40 it seems unlikely that the coronary vasodilating effects of 842 verapamil account for the effects on [K']e and pH, at least in the center of the ischemic zone.…”
Section: Resultsmentioning
confidence: 99%
“…'9 Verapamil dilates the coronary vasculature,38 but no consistent effect on blood supply to an ischemic area has been demonstrated. 21 38 Diltiazem has been shown to improve blood flow to partially perfused areas in the pig,39 but no effects on blood flow to severely ischemic areas were seen. In view of these findings and the minimal collateral circulation in the swine heart,40 it seems unlikely that the coronary vasodilating effects of 842 verapamil account for the effects on [K']e and pH, at least in the center of the ischemic zone.…”
Section: Resultsmentioning
confidence: 99%
“…The observation that verapamil and cardioplegia do not directly inhibit calcium entry on reperfusion is in contrast to many studies (Wende et al, 1975;Reimer et al, 1977;Smith et al, 1977;Lefer et al, 1979) which have shown that, when given prior to a period of ischemia, calcium antagonists delay or prevent tissue damage, and also reduce calcium accumulation Witts et al, 1979;Lefer et al, 1979;Nayler et al, 1980). There are fewer reports of the effects of calcium antagonists given after the onset of ischemia.…”
Section: Camentioning
confidence: 94%
“…Verapamil and other calcium antagonists block the slow calcium current of the action potential (Kohlhardt et al, 1972a(Kohlhardt et al, , 1972bCranefield et al, 1974;Kohlhardt and Mnich, 1978;Henry, 1980). When these drugs are given prior to or at the onset of a period of ischemia, they have been shown to preserve tissue ultrastructure (Reimer et al, 1977), to reduce enzyme release (Wende et al, 1975;Smith et al, 1977;Lefer et al, 1979), to diminish S-T elevation (Lefer et al, 1979;Selwyn et al, 1979), to improve hemodynamic function (Magee et al, 1979;Clark et al, 1979), to maintain tissue ATP (Lefer et al, 1979;Watts et al, 1979;Nayler et al, 1980;Weishaar and Bing, 1980), and to prevent calcium accumulation in whole tissue and isolated mitochondria Watts et al, 1979;Lefer et al, 1979;Nayler et al, 1980). The uniformly beneficial results obtained in such experiments are in sharp contrast to the results of experiments in which calcium antagonists have been administered, not prior to ischemia, but either after the ischemic myocardium has ceased to contract or at the time of reperfusion.…”
mentioning
confidence: 99%
“…In an experimental preparation of isolated hearts, inhibition of Ca2+ influx across the sarcolemma was indicated as the principal mechanism of the myocardial protection observed. ' 10-13 In contrast, in studies of open-chest dogs receiving the drug systemically, the importance of direct effects on the ischemic myocardium remained unclear.3`6 The effects of the drug on the collateral circulation and on peripheral hemodynamics have also been shown to influence the balance of oxygen demand and supply, 5 1 obscuring the direct effects on the jeopardized myocardium.…”
mentioning
confidence: 99%